Effective Administration of Rituximab in Anti-MDA5 Antibody–Positive Dermatomyositis with Rapidly Progressive Interstitial Lung Disease and Refractory Cutaneous Involvement: A Case Report and Literature Review - Yuka Ogawa; Dai Kishida; Yasuhiro Shimojima; Koichi Hayashi; Yoshiki Sekijima (Case Reports in Rheumatology)
We describe the case of a 48-year-old man with dermatomyositis (DM) who demonstrated rapidly progressive interstitial lung disease (RP-ILD) and refractory cutaneous involvement together with high levels of anti-melanoma differentiation-associated gene 5 antibody (anti-MDA5-Ab). Even after combination immunosuppressive therapy including a corticosteroid, cyclosporine A, and intravenous cyclophosphamide, his respiratory insufficiency and cutaneous involvement progressively worsened. However, the administration of rituximab (RTX) resulted in clinical remission as well as a visible reduction in anti-MDA5-Ab levels, suggesting that RTX could be a useful remedy in cases refractory to conventional immunosuppressive agents, especially those of RP-ILD related to anti-MDA5-Ab–positive DM.